Adaptive selective cuckoo search algorithm for multi-objective short-term hydrothermal scheduling - Nguyen, Trung Thang; Truong, Viet Anh; Ha, Trieu Phu (Journal of Technical Education Science, 2017)
This research proposes an Adaptive Selective Cuckoo Search Algorithm (ASCSA) for solving the multi-objective short-term hydrothermal scheduling (MOSTHTS). The main objective of the MOSTHTS problem is to minimize both total power generation cost and emission of thermal generators over a scheduling period while satisfying power balance, hydraulic, and generator operating limit constraints. The proposed ASCSA method is developed for the problem based on improvements from the conventional CSA method to improve the optimal solution and speed up the computational process. The result comparisons from different test systems have indicated that the proposed method can obtain higher quality solution and shorter computational time than many other methods. Therefore, the proposed ASCSA method can be a new efficient method for solving multi-objective short-term HTS problem.